Monster - Sakamoto, Ryūichi 1952-2023 (Well Go USA Entertainment, 2023)
"After a mother discovers that a teacher’s bullying is behind her young son’s sudden strange behavior, she storms into his school demanding an explanation. Continually left without satisfactory answers―and with an increasingly distressed child―she furiously escalates her concerns to the school board and the media. But as the story unfolds through the multilayered perspectives of mother, teacher, and child, the real truth gradually emerges―and proves much more complex than anyone could have expected." [diabolikdvd.com]
Original: Japan 2023
Bonus features: English language available ; trailer
Bildformat 16:9
Keywords: Film; Blu-Ray-Disc